Implementation Of Breast Massage To Increase Breast Milk Production Of Post Partum Mothers In The Oesapa Community Health Center Area - Mokola, Clarra Styvani; Kapitan, Meiyeriance; Kleden, Simon Sani (Jurnal EduHealth, 2025)
Menstruation is a natural biological process that occurs in females during their reproductive years. However, many young girls lack adequate knowledge about menstruation, leading to fear and misconceptions. This study aimed to investigate the effectiveness of health education through video on improving knowledge about menstruation among elementary school students. A pre-experimental one-group pre-test post-test design with proportional random sampling was employed. The study involved 38 female students from SD Negeri 2 and SD Negeri 4 Penebel in April 2024. Data was collected using a questionnaire. The Shapiro-Wilk test was used to assess normality due to the small sample size (n<50). The p-value (p>0.05) indicated normal distribution of the knowledge scores. The mean score before health education was 58.68. The mean scores for posttest week 1 and week 2 were 82.89 and 87.24, respectively. Statistical analysis revealed a significant difference in knowledge scores (p=0.000), demonstrating the effectiveness of the health education intervention. The study highlights the importance of health education in improving knowledge about menstruation among elementary school students. Schools should incorporate menstruation education into their curriculum to empower girls with accurate information and dispel misconceptions.